Low power adiabatic CMOS circuits - Ng, Kim Wee. (2008)
Power consumption has become a critical concern in the design of digital CMOS circuits. While long being neglected, the topic of low power digital design has vaulted to the forefront of the attention in recent years. This thesis reports on the design of a new class of circuits which can overcome the CV^2f barrier faced by the conventional CMOS logic. Known as the adiabatic or energy recovery logic, it uses the technique of recovering energy that would otherwise be dissipated as heat in order to reduce the power dissipation in digital CMOS circuits. To achieve that, ramp-like power clock signals are required to power-up the circuits. In addition, it does not require a specialized MOS fabrication process (unlike other low power approaches such as that of ultra-low threshold voltage and supply).